Resistance to β-Lactams in Neisseria ssp Due to Chromosomally Encoded Penicillin-Binding Proteins - André Zapun; Cécile Morlot; Muhamed-Kheir Taha (MDPI AG, 2016)
Neisseria meningitidis and Neisseria gonorrhoeae are human pathogens that cause a variety of life-threatening systemic and local infections, such as meningitis or gonorrhoea. The treatment of such infection is becoming more difficult due to antibiotic resistance. The focus of this review is on the mechanism of reduced susceptibility to penicillin and other β-lactams due to the modification of chromosomally encoded penicillin-binding proteins (PBP), in particular PBP2 encoded by the penA gene. The variety of penA alleles and resulting variant PBP2 enzymes is described and the important amino acid substitutions are presented and discussed in a structural context.